2009
DOI: 10.1111/j.1749-4486.2009.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the nasal index and the significance of the shape and size of the nose in rhinology

Abstract: Nasal proportions are important aesthetically but appear to have little relevance to the rhinologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 58 publications
8
38
0
Order By: Relevance
“…(37,44,53) In addition, our preliminary reports revealed that Latin Americans and Caucasians have comparable SA:V, and the NI for Asians and Latin Americans were also similar.…”
Section: Nasal Particle Distribution Across Ethnic Groupssupporting
confidence: 52%
See 2 more Smart Citations
“…(37,44,53) In addition, our preliminary reports revealed that Latin Americans and Caucasians have comparable SA:V, and the NI for Asians and Latin Americans were also similar.…”
Section: Nasal Particle Distribution Across Ethnic Groupssupporting
confidence: 52%
“…(36) In the absence of pathological abnormalities, anthropologists believed that variations in normal nasal shapes and sizes of the external nose were due to evolutionary adaptation of humans to climatic conditions. (37,38) Specifically, the ratio between the width and height of the external nose, known as the ''nasal index'' has been reported to correlate with geographic regions: (39) the ''platyrrhine'' (broad-nose) nasal index, described as a typical nose of the African race is associated with a hot, moist climate; a typical Caucasian nose, classified as ''leptorrhine'' (narrow-nose) nasal index is associated with a cold, dry climate; and a classic Asian nose is considered medium sized and is classified as ''mesorrhine''. (38)(39)(40) In addition, studies have reported that the internal nasal morphology of Caucasians tend to be narrower and longer than AfricanAmericans (Blacks).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Nasal parameter: As shown in [ Table 1] In age group (18)(19)(20)(21)(22)(23)(24)(25) the mean values of NL and ND for females significantly different from the males, P< 0.05 while that of NH and NB are not significantly different P> 0.05. Nasal indexes (NI) on living head between 85 and 99.9 is Platyrrhine and those from 100 and above are hyperplatyrrhine therefore for female between ages 18-25 they are found to be Platyrrhine (94.58) and male to be hyperplatyrrhine (100) .…”
Section: Resultsmentioning
confidence: 99%
“…The nasal index (NI), expressed as the percentage ratio of breadth and height of the nose, is one of the most commonly used anthropometric parameters in classifying human races [19,20]. In anthropology and forensic medicine Nasal proportions, together with other physical characteristics, such as skin color and hair texture are used to identify the different 'races' [21]. Not only the race but also sex of an individual or group whose identity is unknown, might be determined using the nasal index [15].Nasal index is also useful in the analysis and classification of fossil remains as well as the study of living population [22].…”
Section: Introductionmentioning
confidence: 99%